Differences in Temperature Changes in Premature Infants During Invasive Procedures in Incubators and Radiant Warmers. (30th November 2017) - Handhayanti, Ludwy; Rustina, Yeni; Budiati, Tri
ABSTRACT: Premature infants tend to lose heat quickly. This loss can be aggravated when they have received an invasive procedure involving a venous puncture. This research uses crossover design by conducting 2 intervention tests to compare 2 different treatments on the same sample. This research involved 2 groups with 18 premature infants in each. The process of data analysis used a statistical independent t test. Interventions conducted in an open incubator showed a p value of .001 which statistically related to heat loss in premature infants. In contrast, the radiant warmer p value of .001 statistically referred to a different range of heat gain before and after the venous puncture was given. The radiant warmer saved the premature infant from hypothermia during the invasive procedure. However, it is inadvisable for routine care of newborn infants since it can increase insensible water loss.